A Unifying Theory of Systems Thinking with Psychosocial Applications. (September 2015) - Cabrera, Derek; Cabrera, Laura; Powers, Erin
<x xml:space="preserve">Abstract</x> Systems thinking is a field characterized by a baffling array of methods and approaches. We posit that underlying all, however, are four universal rules called DSRP (distinctions, systems, relationships, and perspectives; each containing two co‐implying elements). We make distinctions between and among things and ideas, each implying the existence of an other. We identify systems, which are composed of parts and wholes. We recognize relationships composed of actions and reactions. We take perspectives consisting of a point (from which we see) and a view (that which is seen). We argue that DSRP offers a unifying and organizing principle for the field of systems thinking and an indispensable analytical tool for solving complex problems. At the same time, the metacognitive practice of applying these rules has significant psychosocial implications, such as increasing self‐awareness, empathy, and a sense of belonging, while decreasing stereotyping and self‐harming and other‐harming orientations. As such, DSRP has the potential to create advanced analytical thinkers with prosocial orientations. Copyright © 2015 John Wiley & Sons, Ltd.